Grandma knows best: Family structure and age of diagnosis of autism spectrum disorder. (April 2018) - Sicherman, Nachum; Loewenstein, George; Tavassoli, Teresa; Buxbaum, Joseph D
This pilot study estimates the effects of family structure on age of diagnosis, with the goal of identifying factors that may accelerate or delay diagnosis. We conducted an online survey with 477 parents of children with autism. In addition, we carried out novel, follow-up surveys of 196 "friends and family, " who were referred by parents. Family structure and frequency of interactions with family members have significant effects on age of diagnosis (p < 0.05). In all, 25% of parents report that other individuals indicated that their child might have a serious condition before they themselves suspected it. Moreover, around 50% of friends and family report that they suspected that the child had a serious condition before they were aware that either parent was concerned, suggesting that the clues were there to see, especially for experienced viewers. While half of those individuals shared their concerns with the parents, the other half either did not raise any concern (23%) or just "hinted" at their concern (27%). Among children with siblings, children with an older sibling are diagnosed approximately 10 months earlier (p < 0.01) than those without, and children with no siblings were diagnosed 6–8 months earlier than children with siblings (p < 0.01). Interestingly, frequent interactions with grandparents, especially grandmothers, significantly lowered the age of diagnosis by as much as 5 months (p < 0.05). While this pilot study requires replication, the results identify potential causes for accelerated or delayed diagnosis, which if better understood, could ultimately improve age of diagnosis and treatment, and hence outcomes.